The Extent of Engagement in Global Value Chains by Firms in Rwanda - Frazer, Garth (World Bank, Washington, DC, 2019)
Using administrative data for an exhaustive sample of formally registered firms, reveals that the engagement of Rwandan firms in global value chains (GVCs) is remarkably limited. The paper documents several patterns of firm-level exports and compares firm characteristics between exporters and non-exporters. It also illustrates which firm-level characteristics are good predictors for a variety of extensive margins of export and import activities. The analysis includes firms from three goods-producing sectors, agriculture, mining, and manufacturing, but focuses mostly on manufacturing firms. The results indicate large differences between small and large exporters in terms of export market participation, type of products exported, and destinations served. GVC engagement has increased over the 2008-2016 sample period, especially for manufacturing firms, but this is a slow process with frequent set-backs.